2020
DOI: 10.3389/fcell.2020.00436
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Autophagy by Pterostilbene Contributes to the Prevention of Renal Fibrosis via Attenuating NLRP3 Inflammasome Activation and Epithelial-Mesenchymal Transition

Abstract: Chronic kidney disease (CKD) is recognized as a global public health problem. NLRP3 inflammasome activation has been characterized to mediate diverse aspect mechanisms of CKD through regulation of proinflammatory cytokines, tubulointerstitial injury, glomerular diseases, renal inflammation, and fibrosis pathways. Autophagy is a characterized negative regulation mechanism in the regulation of the NLRP3 inflammasome, which is now recognized as the key regulator in the pathogenesis of inflammation and fibrosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 29 publications
6
42
0
Order By: Relevance
“…Additionally, NLRP3 inhibition could attenuate obesity-related kidney disease [ 52 ]. A novel agent pterostilbene , an analog of resveratrol with autophagy-inducing effects, has shown its renal protective effects in an invitro study of urate nephropathy by down-regulating the NLRP3 inflammasome [ 53 ].…”
Section: Cytokinesmentioning
confidence: 99%
“…Additionally, NLRP3 inhibition could attenuate obesity-related kidney disease [ 52 ]. A novel agent pterostilbene , an analog of resveratrol with autophagy-inducing effects, has shown its renal protective effects in an invitro study of urate nephropathy by down-regulating the NLRP3 inflammasome [ 53 ].…”
Section: Cytokinesmentioning
confidence: 99%
“…Resveratrol, the most widely studied stilbene, possesses the ability to attenuate particulate matter (PM 2.5 )-induced cytotoxity in PM 2.5 -treated BEAS-2B cells via inhibiting autophagy, which is an evolutionarily conserved cellular process facilitating the clearance of NLRP3 activators such as β-amyloid and damaged mitochondria, thus suppressing the NLRP3 inflammasome activation (Nakahira et al, 2011;Cho et al, 2014). Pterostilbene, a dimethylated analog of resveratrol, can also markedly augment autophagy to inhibit NLRP3 inflammasome activation, thereby reducing the TGF-β triggered expression of EMT markers including E-cadherin, fibronectin and α-SMA in immortalized rat kidney proximal tubular epithelial cells (NRK-52E cells) (Wang et al, 2020d). Polydatin, a resveratrol glucoside, is able to decrease the expression of a-SMA, collagen Ⅰ, and Ⅲ in human lung epithelial BEAS-2B cells, however, the inhibitory effect of which can be reversed by overexpression of NLRP3.…”
Section: Stilbenesmentioning
confidence: 99%
“…The stilbenes also improve organ fibrosis in vivo. In models of potassium oxonate (PO)-induced hyperuricemia and high adenine diet (HAD)-induced chronic kidney disease (CKD), pterostilbene-triggered autophagy has an attenuating effect on the improvement of renal function and interstitial fibrosis via restraining EMT-mediated NLRP3 inflammasome activation (Wang et al, 2020d). Resveratrol is effective at alleviating lung inflammation and fibrosis caused by particulate matter (PM 2.5 ) via inhibiting autophagy-related NLRP3 inflammasome activation in BALB/c mice (Ding et al, 2019).…”
Section: Stilbenesmentioning
confidence: 99%
“…In this regard, pterostilbene (PTE, trans-3,5-dimethoxy-4-hydroxystilbene), a naturally occurring analog of resveratrol and is a stilbene compound with many health benefits, was used in the study. The protective effects of PTE include its antioxidant activity, anti-inflammatory effects, anti-obesity, and chemopreventive effects, which are attributed to its unique structure [ 13 , 14 , 15 ]. Current studies also indicated the modulation effects of PTE on the immune response.…”
Section: Introductionmentioning
confidence: 99%